Subcutaneous lipectomy by aspiration. - Fossati, Guillermo (Cirugía del Uruguay, 1985)
The subcutaneous lipectomy by aspiration is a surgícal technique permitting resection of pure fatty tissue, by less traumatic means than !hose used thus far.